Selected writings on race and difference - Hall, Stuart 1932-2014 (Stuart Hall: selected writings, 2021)
In Selected Writings on Race and Difference, editors Paul Gilroy and Ruth Wilson Gilmore gather more than twenty essays by Stuart Hall that highlight his extensive and groundbreaking engagement with race, representation, identity, difference, and diaspora. Spanning the whole of his career, this collection includes classic theoretical essays such as "The Whites of Their Eyes" (1981) and "Race, the Floating Signifier" (1997). It also features public lectures, political articles, and popular pieces that circulated in periodicals and newspapers, which demonstrate the breadth and depth of Hall's contribution to public discourses of race. Foregrounding how and why the analysis of race and difference should be concrete and not merely descriptive, this collection gives organizers and students of social theory ways to approach the interconnections of race with culture and consciousness, state and society, policing and freedom